(untitled) (International Journal of Engineering and Computer Science, 2018)
: As wireless sensor network applications are the emerging trend for the recent technologies. The wireless sensor network works on the backbone of the network called sensor nodes, a tiny device having different components, a sensor unit, an ADC (Analog to Digital Converter), a CPU (Central Processing Unit), a power unit and a communication unit. A wireless sensor network (WSN) consist of hundreds to thousands of low power multi-functional sensor nodes work in an unattended environment and have sense, computation and communication ability. The main aim of the sensor nodes is data communication, means transfer of data packs from one node to other with in the network. This communication is done using clustering and average energy of a node. Each cluster selects a leader called cluster head. The cluster heads CHs are selected on the basis of average energy and the probability. There are number of clustering protocols used for the cluster Head selection, The main concept is the life time of a network which depends upon the average energy of the node. In this work we proposed a model, which uses the residual energy for cluster head selection and LZW compression Technique during the transmission of data packets from CHs to base station. This technique improves the throughput and life time of network and saves the energy of node during transmission and helps to transfer more data in less energy consumption. The Proposed protocol is called COMPRESSED MODLEACH.